2022
DOI: 10.3389/fpls.2022.832034
|View full text |Cite
|
Sign up to set email alerts
|

Genome Skimming Contributes to Clarifying Species Limits in Paris Section Axiparis (Melanthiaceae)

Abstract: Paris L. section Axiparis H. Li (Melanthiaceae) is a taxonomically perplexing taxon with considerable confusion regarding species delimitation. Based on the analyses of morphology and geographic distribution of each species currently recognized in the taxon, we propose a revision scheme that reduces the number of species in P. sect. Axiparis from nine to two. To verify this taxonomic proposal, we employed a genome skimming approach to recover the plastid genomes (plastomes) and nuclear ribosomal DNA (nrDNA) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 93 publications
(140 reference statements)
1
13
0
Order By: Relevance
“…2 ) resolved both species as fully supported monophyletic entities (BS = 100%), and the two species were phylogenetically distinct from each other in the tree topology. Similar to previous studies [ 49 , 55 ], ML analysis of the nrDNA arrays generated tree topologies that were completely different from the plastome phylogeny (Fig. 3 ).…”
Section: Resultssupporting
confidence: 83%
“…2 ) resolved both species as fully supported monophyletic entities (BS = 100%), and the two species were phylogenetically distinct from each other in the tree topology. Similar to previous studies [ 49 , 55 ], ML analysis of the nrDNA arrays generated tree topologies that were completely different from the plastome phylogeny (Fig. 3 ).…”
Section: Resultssupporting
confidence: 83%
“…This study describes a protocol for rapidly obtaining a primary species delimitation scheme. In some cases, plastome data contributes to discovering cryptic diversity or sorting out problematic taxonomic treatments [ 24 , 74 , 75 ], and have formed the primary basis of formal taxonomic revisions [ 25 , 76 ]. In other cases, an integrative strategy including plastome data has been applied for delimiting species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a couple of dozen samples can be sequenced and combined with hundreds of previously available sequences to produce a densely sampled new phylogeny (Mo et al, 2022 ). Recent studies have shown that an increase in the number of plastid loci and nrDNA greatly improves the resolution of phylogenetic trees for taxonomically difficult groups, although unresolved relationships may remain (Loiseau et al, 2021 ; D'haijère et al, 2022 ; Fu et al, 2022 ; Ji et al, 2022 ). The lower resolution might result from missing data due to the varying sequencing coverage in genome skimming data, or actual low informativeness that might not be sufficient to resolve some evolutionary relationships, resulting in phylogenies that are less resolved toward the tips.…”
Section: Genome Skimmingmentioning
confidence: 99%